HPLC profile of root extract of Costus Malortieanus / Ahmad Fathi Mahayudin - Mahayudin, Ahmad Fathi (2010)
Costus malortieanus was chosen as the material for this study. Only root extract was selected in this report. The objective of this study is to develop an efficiency method for isolation of plants constituents and to obtain the best possible chromatography profile of root extract of Costus malortieanus by using HPLC. All analyses were carried out in a reverse phase mode using an ODS Hypesil Column (150x4.6mm, 5 μm particle size, thermo electron corporation) with a guard column filled with the same material. The column temperature was maintained at 36oC. The DAD detects a full UV spectrum (190nm to 400nm). The mobile phase consisted of purified water (solvent A) and acetonitrile (solvent B). The analysis were carried out at flow rate of 1ml/min. Then, elution programs were designed in order to get best possible chromatography profile. For this study retention time of mobile phase was manipulated. It was found that chromatographic elution program 4 shows the best results for the compound separation. Methanol extract of root of Costus malortienous was successfully achieved using HPLC system with UV detector of 320 nm wavelengths